Protein interactions with self-assembled monolayers presenting multimodal ligands a surface plasmon resonance study - Vutukuru, Srinavya (Langmuir : the ACS journal of surfaces and colloids, 2006)
This paper describes the use of surface plasmon resonance (SPR) spectroscopy and self-assembled monolayers (SAMs) to understand the characteristics of surfaces that promote the adsorption of proteins at high ionic strengths (high-salt conditions). We synthesized SAMs presenting different multimodal ligands and determined the influence of surface composition, solution composition, and the nature of the protein on the extent of protein adsorption onto the SAMs. Our results confirm that hydrophobic interactions can contribute significantly to protein adsorption under high-salt conditions. In particular, the extent of protein adsorption under high-salt conditions increased with increasing surface hydrophobicity. The extent of protein adsorption was also influenced by the solution composition and decreased with an increase in the chaotropicity of the anion. The combination of SPR and SAMs is well-suited for studying the interaction of proteins with complex surfaces of relevance to chromatography